Dominasi Tindak Tutur Berbahasa Inggris dalam Sosial Media sebagai Strategi Promosi - Viklous, Belinda Ekharisti; Wijana, I Dewa Putu (ELTIN Journal, 2024)
This study examines the types and the strategies of expressive speech acts employed on Agnes Monica’s Instagram account. The method used for this research is qualitative research with a descriptive explanation. The results of the data that the researchers have collected and analyzed are from 140 data, there are 16 kinds of expressive speech acts with the most dominant function being “excited” with 18%, and it classified into 5 strategies of expressive speech acts with the dominant strategy being “implicit, direct, literal, and expressed” with 40%. The researcher also found some factors that influence English expressive speech acts on @agnezmo Instagram where Agnes Monica is described as a modern society with the characteristics of having a high level of mobility who pursuing her career internationally, tries to communicate globally by using a language that can be understood widely, and getting affected by the social culture surroundings. These factors influenced the lifestyle and language habits of Agnes Monica. Also, they became one of the strategies that Agnes used in branding and promoting her works through social media to be welcomed by the international market.